Comparative Analysis of Clinical Outcomes and Procedural Costs between the Conventional Two-stage Technique and 4D Brachytherapy for Early Prostate Cancer. Issue 1 (January 2018) - Langley, S.E.M.; Uribe, J.; Uribe-Lewis, S.; Money-Kyrle, J.; Perna, C.; Khaksar, S.; Soares, R.; Laing, R.
Abstract: Aims: To assess long-term outcomes and resource use of 4D Brachytherapy, a one-stage real-time implant for the treatment of prostate cancer that uses stranded and loose iodine-125 seeds, and to compare with the conventional two-stage (2S) technique. Materials and methods: Prospectively collected data of men who underwent 2S and 4D low dose rate brachytherapy in a single institution were analysed. Survival estimates were analysed using the Kaplan–Meier method and Log-rank test. Treatment failure rates were further compared by Cox proportional hazards (Coxph) regression or by a surrogate prostate-specific antigen value cut-off of 0.4 ng/ml 48 months post-implant. Treatment toxicity outcomes were also evaluated. Comparative costs were based on published English National Health Service data. Results: We compared outcomes of 690 men treated with 2S and 1031 men with 4D brachytherapy. Median follow-up times were 10.4 and 5.2 years ( P  < 0.001) for 2S and 4D cases, respectively. Day 0 post-implant dosimetry was improved in 4D brachytherapy patients. Five years post-implant ≥98% of cases were alive and ≥95% were free from disease relapse irrespective of technique. Coxph regression showed the risk of relapse after 4D brachytherapy was similar to the 2S technique (hazard ratio 0.67, 95% confidence interval 0.44–1.03, P  = 0.065). Forty-eight months post-implant there was a significantly greater proportion of 4D brachytherapy cases with a prostate-specific antigen below 0.4 ng/ml relative to the 2S technique. Urinary and bowel symptom scores showed reduced toxicity after 4D implants and potency conservation was similar to the 2S technique. The reduction in time and resource use decreased the cost of 4D brachytherapy by 40% compared with the 2S technique. Conclusion: Two-stage and 4D brachytherapy are both highly effective for the control of localised prostate cancer. However, relative to the 2S technique, the 4D technique was associated with improved dosimetry, reduced treatment-related toxicity and reduced cost. Further follow-up will assess disease control superiority of 4D brachytherapy beyond 5 years post-implant. Highlights: Low dose rate brachytherapy is a radiation-based treatment for prostate cancer. Two-stage and real-time 4D prostate brachytherapy techniques are compared. Both techniques are highly effective in the control of early prostate cancer. 4D brachytherapy reduces treatment-related toxicity and cost.